2005
DOI: 10.1002/ajmg.b.30132
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the association of a functional serotonin transporter promoter polymorphism with alcohol dependence

Abstract: The neurotransmitter serotonin (5-HT) has been shown to regulate alcohol consumption in both animals and humans. Since activity of the 5-HT transporter protein (5-HTT) regulates 5-HT levels, the gene encoding this protein may contribute to the risk of alcohol dependence (AD). Studies of the association to AD of a functional insertion-deletion polymorphism in the 5-HTT-linked promoter region (5-HTTLPR) have yielded inconsistent results. We conducted a meta-analysis of data from 17 published studies (including 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
180
5
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(195 citation statements)
references
References 53 publications
7
180
5
3
Order By: Relevance
“…This meta-analysis also reported a 15 % greater likelihood of having at least one S allele in patients diagnosed with alcohol dependence (McHugh et al 2010). Another meta-analysis of 17 studies by Feinn et al (2005), reported similar associations between the S allele and alcohol dependence. This study reported an odds ratio of 1.18 (95 % confidence intervals (CI)=1.03-1.33) for the S allele in alcoholdependent subjects; hence an 18 % higher risk for developing alcohol dependence.…”
Section: -Httlpr Polymorphism and Alcohol Use Problemssupporting
confidence: 57%
See 2 more Smart Citations
“…This meta-analysis also reported a 15 % greater likelihood of having at least one S allele in patients diagnosed with alcohol dependence (McHugh et al 2010). Another meta-analysis of 17 studies by Feinn et al (2005), reported similar associations between the S allele and alcohol dependence. This study reported an odds ratio of 1.18 (95 % confidence intervals (CI)=1.03-1.33) for the S allele in alcoholdependent subjects; hence an 18 % higher risk for developing alcohol dependence.…”
Section: -Httlpr Polymorphism and Alcohol Use Problemssupporting
confidence: 57%
“…The unanimity of the authors' conclusions about the LL genotype showing greater propensity for addictive behaviors and problem drinking, as well as the reversal of these symptoms with SSRI medications, suggests a broader hypothesis that decreased serotonin levels could be responsible for addictive behaviors (Dawes et al 2009). Another view is that the S allele is associated with increased alcohol dependence, addictive behaviors, and personality traits like neuroticism (Feinn et al 2005;Herman et al 2003;Munafò et al 2006). The homeostatic effects of serotoninergic systems in genesis, differentiation, and maturation of neurons are thought to be responsible for these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,41,42,58 Clinical association studies have further examined the relationship between SERTLPR alleles and psychiatric disorders and anxiety-related personality traits, [59][60][61][62][63][64][65][66] suicide, 67,68 alcoholism, 69,70 response to antidepressants [71][72][73] and brain function as revealed by MRI scans. [74][75][76][77] Although many studies have reported correlations between SERTLPR alleles and SERT expression levels or clinical phenotype, almost an equal number of studies have not.…”
Section: Discussionmentioning
confidence: 99%
“…8,154 On the other hand, there appears to be some degree of specificity as no G Â E was identified for generalised anxiety disorder or anxiety symptoms. 15,34 While 5-HTTLPR genotype is not reliably directly associated with depression, 151 the more severe and multiple adverse outcomes including violent suicide, 155,156 suicide attempts among alcohol-dependent subjects 157 and comorbid alcohol dependence with depression 158,159 are directly associated with 5-HTTLPR s allele loading. Although a meta-analysis reported a weak association between 5-HTTLPR s allele and alcoholism per se, 158 this association was driven by samples with comorbid mental health problems.…”
Section: Genetic Control Of the Environmentmentioning
confidence: 99%